Analisis Yuridis Asas Praduga Tidak Bersalah Pada Sistem Peradilan Pidana Dalam Perspektif Hak Asasi Manusia - Mang Tra Himam Idayat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The presumption of innocence is a fundamental principle in the criminal justice system that serves to protect the rights of the accused from the risk of unfair punishment. This principle states that a person is presumed innocent until proven legally and convincingly guilty of committing a crime before a court. This research uses an empirical juridical method, namely a legal approach that examines how positive law, especially unwritten law, is applied in society. In this context, the research highlights the implementation of the presumption of innocence in criminal justice practices in Indonesia. The application of the presumption of innocence is very important for the judicial process to run fairly, directed, and achieve the main objectives of criminal justice, namely upholding justice, legal certainty, and legal order. The relationship between this principle and human rights is very close, because with this principle, suspects and defendants are guaranteed to obtain legal protection during the legal process. Rights such as not being treated as guilty before a court decision, the right to defense, and the right to humane treatment are part of this principle. Enforcing the presumption of innocence is not only the responsibility of law enforcement officers such as the police, prosecutors, and judges, but also all elements of society. Therefore, it is crucial for every citizen to understand and respect this principle in their social lives, especially in responding to ongoing legal cases. As a concrete implementation, law enforcement must implement policies that protect the public and maintain a sense of security, for example by increasing surveillance in crime-prone areas. This way, the law can be enforced fairly, and public trust in the criminal justice system will increase. The presumption of innocence is a crucial foundation for the creation of humane and fair trials in Indonesia.